Human rights and the political: Assessing the allegation of human rights overreach in migration matters - Farahat, Anuscheh (Netherlands Quarterly of Human Rights, 2022)
Europe's external borders have been the site of intense human rights struggles over the last decade. While States are inventing ever new practices to circumvent their human rights responsibility by not responding to rescue calls or using private actors as proxies for refoulement, human rights activists seek to expand State jurisdiction to effectively hold European governments responsible for human rights violations at their borders and on the high seas. At the same time, the rise of populist movements and increasing xenophobia have made expansive human rights interpretation to the benefit of migrants increasingly suspicious in public discourse. The question therefore arises: Does the expansion of migrants' human rights and State responsibility bear features of 'human rights overreach' in the sense that human rights encroach too much on State sovereignty, which may ultimately decrease the acceptance of human rights themselves? Or is it a necessary 'outreach' of human rights, that is, an adaptation of human rights to new practices of border protection in order to ensure human rights' effectiveness? This paper addresses these questions in three steps. It first briefly presents current struggles about migrants' human rights in the Mediterranean. It then deals with the increasing critique of human rights overreach in migration matters and assesses judicial practice in reaction to increasing State pressure. The core argument finally developed in this paper is that we should respond to the allegation of overreach by advancing a more political understanding of human rights, which acknowledges the methodological limits of regressive human rights interpretation and defends the idea of human rights as a concrete utopia. The paper develops this argument with a view to the concrete case law on migration issues and suggests how courts and migration law scholars should deal with the challenges of human rights struggles regarding migration.
CRIS-Team WoS Importer:2022-04-22
Keywords: Migration law; migrants’ human rights; evasion of human rights; extraterritorial applicability of human rights; human rights overreach; transformative human rights; human rights regression; human rights courts; push-backs at sea